Bibliometric Analysis of Anti-Money Laundering (AML) in the Financial Sector - Judijanto, Loso (Westscience Press, 2025)
This study presents a bibliometric analysis of research on Anti-Money Laundering (AML) within the financial sector, aiming to provide a systematic overview of the field's development, key themes, and intellectual structure. Using data from the Scopus database, the study analyzes publication trends, co-authorship networks, keyword co-occurrences, and country collaborations from 2000 to 2024. The findings reveal a growing emphasis on digital finance technologies, particularly cryptocurrency, blockchain, and artificial intelligence, highlighting the evolving challenges in AML. While traditional themes like financial crime, terrorist financing, and regulatory frameworks remain central, the integration of technological innovations such as AI and blockchain is reshaping AML strategies. The study also identifies key authors, institutions, and global research collaborations that have significantly contributed to AML scholarship. Based on these findings, the paper suggests several directions for future research, including the exploration of emerging technologies in AML systems, cross-border regulatory alignment, and empirical assessments of AML effectiveness. The study underscores the interdisciplinary and global nature of AML research, which is essential for combating financial crimes in an increasingly digital financial landscape.